Case Report: Trichosporon japonicum Fungemia in a Pediatric Patient With Refractory Acute B Cell Lymphoblastic Leukemia - Albitar-Nehme, Sami; Agosta, Marilena; Kowalska, Agata Helena; Mancinelli, Livia; Onori, Manuela; Lucignano, Barbara; Mattana, Giordana; Quagliarella, Francesco; Cefalo, Maria Giuseppina; Merli, Pietro; Locatelli, Franco; Perno, Carlo Federico; et al. (Frontiers in Pediatrics, 2022)
Trichosporon japonicum is a very rare opportunistic yeast causing fungal disease in humans, especially in immunocompromised hosts. Here, we describe a new case of T. japonicum isolated from the blood of a pyrexial pediatric patient with refractory acute B cell lymphoblastic leukemia and acute respiratory distress. Prompt diagnosis through early clinical suspicion and appropriate molecular microbiology analysis allowed the yeast to be accurately identified at species level. Subsequent drug susceptibility testing and focused antifungal treatment with voriconazole and amphotericin B led to a complete clinical and mycological resolution of the infection, which represents the second successful case of T. japonicum bloodstream infection described in literature to date.